2021
DOI: 10.4315/jfp-21-111
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance and Genetic Diversity of Campylobacter spp. Isolated from Broiler Chicken at Three Levels of the Poultry Production Chain in Costa Rica

Abstract: Campylobacter spp. is considered the most common bacterial cause of human gastroenteritis, one of the four main causes of diarrheal disease worldwide, and one of the main foodborne pathogens causing hospitalizations and deaths. A total of 148 strains of Campylobacter spp.   isolated from poultry at farms, processing plants and retail stores in Costa Rica were examined for resistance to six antibiotics. An agar dilution test was used to determine the minimum inhibitory concentration and susceptibility profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…This is in agreement with other studies that showed 30% of false negatives by culture compared to PCR [43]. Polymerase chain reaction results showed a rate of 88%, confirming previously published data on the search for Campylobacter of avian origin in Brazil (100% prevalence) [44], in Costa Rica (80%) [45], and in Sri Lanka (63.8%) [46]. Excessive use of antibiotics could cause culture failure in a high number of false negative cases.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with other studies that showed 30% of false negatives by culture compared to PCR [43]. Polymerase chain reaction results showed a rate of 88%, confirming previously published data on the search for Campylobacter of avian origin in Brazil (100% prevalence) [44], in Costa Rica (80%) [45], and in Sri Lanka (63.8%) [46]. Excessive use of antibiotics could cause culture failure in a high number of false negative cases.…”
Section: Discussionsupporting
confidence: 91%